Guidance for design and endpoints of clinical trials in chronic hepatitis B - Report from the 2019 EASL-AASLD HBV Treatment Endpoints Conference - Cornberg, Markus; Lok, Anna Suk-Fong; Terrault, Norah A.; Zoulim, Fabien; Berg, Thomas; Brunetto, Maurizia R.; Buchholz, Stephanie; Buti, Maria; Chan, Henry L.Y.; Chang, Kyong-Mi; Dandri, Maura; Dusheiko, Geoffrey; et al. (Journal of hepatology, 2020)
Representatives from academia, industry, regulatory agencies, and patient groups convened in March 2019 with the primary goal of developing agreement on chronic HBV treatment endpoints to guide clinical trials aiming to ‘cure’ HBV. Agreement among the conference participants was reached on some key points. ‘Functional’ but not sterilising cure is achievable and should be defined as sustained HBsAg loss in addition to undetectable HBV DNA 6 months post-treatment. The primary endpoint of phase III trials should be functional cure; HBsAg loss in ≥30% of patients was suggested as an acceptable rate of response in these trials. Sustained virologic suppression (undetectable serum HBV DNA) without HBsAg loss 6 months after discontinuation of treatment would be an intermediate goal. Demonstrated validity for the prediction of sustained HBsAg loss was considered the most appropriate criterion for the approval of new HBV assays to determine efficacy endpoints. Clinical trials aimed at HBV functional cure should initially focus on patients with HBeAg-positive or negative chronic hepatitis, who are treatment-naïve or virally suppressed on nucleos(t)ide analogues. A hepatitis flare associated with an increase in bilirubin or international normalised ratio should prompt temporary or permanent cessation of an investigational treatment. New treatments must be as safe as existing nucleos(t)ide analogues. The primary endpoint for phase III trials for HDV coinfection should be undetectable serum HDV RNA 6 months after stopping treatment. On treatment HDV RNA suppression associated with normalisation of alanine aminotransferase is considered an intermediate goal. In conclusion, regarding HBV ‘functional cure’, the primary goal is sustained HBsAg loss with undetectable HBV DNA after completion of treatment and the intermediate goal is sustained undetectable HBV DNA without HBsAg loss after stopping treatment.